Reasoning in Steam Education: Unlocking the Power of Induction, Deduction, and Abduction - Upadhyaya, I. R.; Kaphle, G. C. (Journal of Lumbini Engineering College, 2024)
This article explores the significant role of reasoning within science education, examining three main processes: deductive, inductive and adductive reasoning. It underscores the significance of these cognitive processes in facilitating comprehension of intricate scientific concepts and problem solving in different domains. It also explains how each mode of reasoning can be applied in real world contexts through practical examples obtained from various fields with the emphasis of their relevance and utility in fostering critical analysis and understanding. It explains all the reasoning with the balanced understanding of reader’s effectiveness. The main aim of the article is ti equip the readers with the tools require to make informed decisions and navigate complex issues in both academic and professional spheres. Finally, the articles seek to enhance the students reasoning proficiency, thereby bolstering their critical thinking abilities and contributing to their success in different intellectual pursuits.